(3cJGH aj GdNjds
(3ChdgG (B:s
(3Qhi Yf QShd Gddg Udi Gddg Ydjg hSde Cf QLdkG jSei SdjeGf GdNjd MVQ Edi Hjf jOi GdfHi Udi Gddg Ydjg hSde abGd jG QShd Gddg Efi (B( (3ZGO (B) (3ai TQGA aQS aeGPG CTJQi s
(3BNQgG (B:s
(3hCYde Cfg eG SeM GdReGf HeKd gPG GdcJGH GdEfSGf , fSCdg JYGdi HGdSGOGJ GdCYjGf Cf jfaY Hg aQSGf GdESdGe GdfGUQjf dOjf Gdgd GdeLGgOjf ai SHjd Gddg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs